2013
DOI: 10.1021/nl4000147
|View full text |Cite
|
Sign up to set email alerts
|

Built-in Potential and Charge Distribution within Single Heterostructured Nanorods Measured by Scanning Kelvin Probe Microscopy

Abstract: The electrostatic potential distribution across single, isolated, colloidal heterostructured nanorods (NRs) with component materials expected to form a p-n junction within each NR has been measured using scanning Kelvin probe microscopy (SKPM). We compare CdS to bicomponent CdS-CdSe, CdS-PbSe, and CdS-PbS NRs prepared via different synthetic approaches to corroborate the SKPM assignments. The CdS-PbS NRs show a sharp contrast in measured potential across the material interface. We find the measured built-in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 56 publications
(100 reference statements)
1
45
0
Order By: Relevance
“…

Spatially resolved surface photovoltages pectroscopy (SRSPS) was employed to obtain direct evidence for highly anisotropic photogenerated charge separation on different facets of asingle BiVO 4 photocatalyst. [3][4][5] In recent years,the engineering of semiconductor-based photocatalysts with controlled morphology and preferentially exposed facets has proved an efficient way of improving photocatalytic activity. The surface photovoltage signal intensity on the {011} facet was 70 times stronger than that on the {010} facets.The influence of the builtin electric field in the space charge region of different facets on the anisotropic photoinduced charge transfer in asingle semiconductor crystal is revealed.

Photoinducedchargeseparationonthenano-tomicrometer

scale,with varying lifetimes,constitutes the key component of solar energy conversion devices.

…”
mentioning
confidence: 99%
“…

Spatially resolved surface photovoltages pectroscopy (SRSPS) was employed to obtain direct evidence for highly anisotropic photogenerated charge separation on different facets of asingle BiVO 4 photocatalyst. [3][4][5] In recent years,the engineering of semiconductor-based photocatalysts with controlled morphology and preferentially exposed facets has proved an efficient way of improving photocatalytic activity. The surface photovoltage signal intensity on the {011} facet was 70 times stronger than that on the {010} facets.The influence of the builtin electric field in the space charge region of different facets on the anisotropic photoinduced charge transfer in asingle semiconductor crystal is revealed.

Photoinducedchargeseparationonthenano-tomicrometer

scale,with varying lifetimes,constitutes the key component of solar energy conversion devices.

…”
mentioning
confidence: 99%
“…Nanayakkara et al employed scanning Kelvin probe microscopy to study the band offsets in the CdE/PbE NRs and found large built-in fields that occur at the interface. 20 30 In their reaction, the cation exchange starts at opposite edges of the nanocrystals producing spherical heterostructures that "sandwich" the CuS between ZnS (dual interfaces). The heterostructures presented here are smaller and quantum confined heterostructures with a quasi-spherical shape yet anisotropic composition, which could allow for access to electrons and holes within an amenable packing geometry.…”
mentioning
confidence: 99%
“…These potential differences revealed built-in potentials ranging from 100 to 920 mV for various CdS/Cu 2 S NRs. 137 Recently, Nanayakkara et al 31 directly measured the built-in potential in individual CdS/PbS axial NRs using SKPM. Similar to the work of Zaniewski et al, 137 CdS/PbS NRs were synthesized by a cation-exchange process and deposited on HOPG by spin coating.…”
Section: Built-in Potentialmentioning
confidence: 99%
“…Therefore, the regions with deeper potential relative to the tip (darker color scale) are assigned to PbS regions of the CdS/PbS NR. 31 By comparing potential measurements across singlecomponent CdS, heterostructured CdS/PbS, seeded NR CdSe/CdS, and sequentially grown CdS/PbSe, Nanayakkara et al 31 attributed the potential change across the NRs to the difference in work function of each material. In the nanoscale material interface with the NR, charge exchange occurs to equilibrate the Fermi level in each component, resulting in an electrical potential difference.…”
Section: Built-in Potentialmentioning
confidence: 99%